2001
DOI: 10.1016/s0016-7037(01)00582-8
|View full text |Cite
|
Sign up to set email alerts
|

The solubility of rhenium in silicate melts: Implications for the geochemical properties of rhenium at high temperatures

Abstract: Abstract-The solubility of rhenium (Re) in a haplobasaltic melt (anorthite-diopside eutectic composition) has been experimentally determined using the mechanically assisted equilibration technique at 1400°C as a function of oxygen fugacity (10 Ϫ12 Ͻ fO 2 Յ 10 Ϫ7 bar), imposed by CO-CO 2 gas mixtures. Samples were analysed by laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS). This is a true microanalytical technique, which allows small-scale sample heterogeneity to be detected, while provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
65
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(78 citation statements)
references
References 20 publications
9
65
4
Order By: Relevance
“…These observations are best explained by a late influx of planetesimals of broadly chondritic composition after formation of the Earth's core (Kimura et al, 1974;Chou, 1978;Jagoutz et al, 1979;Morgan et al, 1981;Morgan, 1986;Holzheid et al, 2000;Ertel et al, 2001). Many other explanations have been offered, however, and Drake (2000) recently described the rise and demise of the more notable: inefficient core formation (Jones and Drake, 1986), and lowering of metalsilicate partition coefficients by high temperature (Murthy,199 1) or by a Fe-S-.O liquid composition of the outer core (Brett, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…These observations are best explained by a late influx of planetesimals of broadly chondritic composition after formation of the Earth's core (Kimura et al, 1974;Chou, 1978;Jagoutz et al, 1979;Morgan et al, 1981;Morgan, 1986;Holzheid et al, 2000;Ertel et al, 2001). Many other explanations have been offered, however, and Drake (2000) recently described the rise and demise of the more notable: inefficient core formation (Jones and Drake, 1986), and lowering of metalsilicate partition coefficients by high temperature (Murthy,199 1) or by a Fe-S-.O liquid composition of the outer core (Brett, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…. Partition coefficients for the HSE are at 0.1 MPa, 1573-1673 K and IW-2 from Fe-free experiments by 27 (Re), 44 (Os), 18 (Ir), 45 (Ru), 16 (Pd), 46 (Au), 21 (Pt and Rh). Please click here to view a larger version of this figure.…”
Section: Representative Resultsmentioning
confidence: 99%
“…Quenched silicate runproducts from HSE solubility experiments performed at reducing conditions, however, often display evidence for contamination by dispersed HSE±Fe inclusions 17 . Despite the near ubiquity of these inclusions in low fO 2 experiments containing Pt, Ir, Os, Re and Ru, (e.g., [18][19][20][21][22][23][24][25][26][27] ), there is notable variability between studies in their textural presentation; compare for example references 22 and 26 . Although it has been demonstrated that inclusions can form which are a stable phase at the run conditions of an experiment 28 , this does not preclude the formation of inclusions as the sample is quenched.…”
mentioning
confidence: 99%
“…Recent experimental studies do not favor such high values for D Re (Ertel et al, 2001) and D Pt (Holzheid et al, 2000) compared with D Os (Borisov and Walker, 2000) but further experimental work is needed before a definitive answer can be given to this long-standing problem. Indeed, it was recently suggested that the abundance of moderately siderophile elements in Earth's mantle was set by equilibrium partitioning at model pressures (40 to 60 Gpa) and temperatures (2000 to 4000 K) much higher (Gessmann and Rubie, 2000;Li and Agee, 2001b) than those investigated by partitioning experiments of highly siderophile elements (Borisov and Walker, 2000;Holzheid et al, 2000;Ertel et al, 2001). One might also question whether metal segregated from silicate at uniform pressure and temperature.…”
Section: Discussionmentioning
confidence: 98%
“…One particular problem complicating the interpretation of experimental results is the frequent presence of HSE micronuggets in the silicate glass phase. While some authors (Ertel et al, 2001) view these as experimental artifacts that must be avoided, a very recent study (Cottrell and Walker, 2002) suggests that these micronuggets may in fact be quench products. If true, then the silicate/metal partition coefficient of platinum and rhenium may be several orders of magnitude higher than conventionally assumed.…”
Section: Discussionmentioning
confidence: 99%